Analysis factors related to prisoner's resiliency in Rutan Perempuan kelas IIA Surabaya - Rahmah, Citra Danurwenda; Fitryasari, Rizki; Pradanie, Retnayu (Jurnal Ners, 2022)
Introduction: Staying in prison as a female prisoner will affect her physical and psychological conditions. Psychologically, the emotional state and mental health of women are different from men, and the prevalence of poor mentality among female prisoners is higher. Such a situation can be avoided if the prisoners have good resilience. One of the efforts to increase resilience is to know the factors related to resilience through this research. Methods: This is a correlational study with cross-sectional approach. The population was all prisoners and detainees in Rutan Perempuan Kelas IIA Surabaya with a sample size of 115 respondents. The variables of this study are individual factors (detention status, recidivism, length of detention, latest education, previous employment, and criminal acts committed), emotional regulation, social support, stigma, and resilience. The data were collected using a questionnaire and analyzed using multiple linear regression. Results: There is a relationship which shows that emotional regulation (p = 0.012; r = 1.223), social support (p =0.003; r = 1.363) can increase resilience while stigma (p = 0.010; r = -1.383) can reduce the level of resilience in prisoners and prisoners. Meanwhile, individual factors were not associated with resilience (p = 0.596; 0.627; 0.298; 0.170; 0.857; 0.457). Conclusions: Increasing resilience in prisoners and detainees can be achieved by increasing emotional regulation and social support as well as reducing stigma against prisoners and detainees by doing the active participation of prisoners and detainees, detention center officers, and families or people closest to inmates and holding a positive activity within the prison.